Competition between green self-trapped-exciton and red non-bridging-oxygen emissions in SiO2 under interband excitation. Issue 1 (December 2018) - Paleari, Alberto; Meinardi, Francesco; Brovelli, Sergio; Lorenzi, Roberto
Abstract The knowledge advancement in the physics of silicon dioxide has promoted ground-breaking progress, from microelectronics to fibre optics. However, the SiO2 exciton decay mechanism is still mostly unrevealed. Here, we analyse the temperature dependence of interband-excited luminescence and the reflectivity by means of synchrotron radiation on a wide selection of SiO2 materials. This enables us to decouple the band-to-band recombination steps from non-radiative decay pathways that typically mask the relaxation mechanisms. We show that band-to-band excitations decay into two competitive correlated channels leading to green and red luminescence so far ascribed to independent transitions. Here we discuss the assignment to a dual relaxation route involving either 'free' or 'interacting' non-bridging-oxygen sites. Such an interpretation suggests an explanation for the elusive non-bridging-oxygen centres in quartz. The reflectivity spectra finally demonstrates a general relationship between exciton spectral position and bandwidth in SiO2 and clarifies the role of disorder in exciton localization. Silicon dioxide is a crucial material in the world of photonics but aspects of its optical decay mechanisms are still not fully understood. The authors use synchrotron radiation to analyse emission processes for different types of silica and quartz and deduce by what mechanisms they may occur.